Determination of flavonoid components from Morinda citrifolia (Mengkudu) and their antioxidant activities - Saidin, Saidatul Husni; Yusuf, Umi Kalsom; Rahmat, Asmah; Muhammad Sukari, Aspollah (Universiti Putra Malaysia Press, 2005)
Five flavonoid components were isolated and identified from Morinda citrifolia's leaves; quercetin 3,7-0-dimethyl ether, quercetin 3-0-methyl ether, kaempferol 3,4'-0-dimethyl ether, kaempferol 5, 7-0-diarabinoside and apigenin. The isolation of flavonoid components was carried using paper chromatography methods with three different system solutions namely, BAW (n-butanol:acetic acid.water; 4:1:5), 15% acetic acid (15% HoAc), BEW (n-butanol:ethanol:water; 4:1:2.2) in addition to pare water. Flavonoid was identified through their colors under ultra violet (UV) with/without NH3, Rf values, acid hydrolysis to aglycone and sugar, co-chromatographic comparison with standard markers and spectral analysis by using a series of shift reagents. All of these flavonoid components were firstly reported in the genus Morinda. The antioxidant activities of flavonoid components were evaluated by using the ÃŸ-carotene bleaching method. Butylated hydroxyl toloul (BHT) and quercetin were used as positive markers. All isolated flavonoid components showed declining antioxidant activities through out the experiment. At the 40th minute, quercetin 3-0-methyl ether showed the highest antioxidant activities (77.67%); followed by quercetin 3,7-0-dimethyl ether (77.00%), kaempferol 3,4â€™-0 dimethyl ether (66.47%), apigenin (58.10%) and kaempferol 5,7-0-diarabinoside (56.14%). Statistical analysis was done using ANOVA with SPSS version 11.0 software. The results showed that all antioxidant activities belonging to the flavonoid components were significantly different from BHT and quercetins' antioxidant activites (p < 0.05).